2010
DOI: 10.1108/01439911011018920
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel audio biofeedback for dynamical coupling between prosthetic hands and their users

Abstract: It is widely agreed that amputees have to rely on visual input to monitor and control the position of the prosthesis while reaching and grasping because of the lack of proprioceptive feedback. Therefore, visual information has been a prerequisite for prosthetic hand biofeedback studies. This is why, the underlying characteristics of other artificial feedback methods used to this day, such as auditive, electro-tactile, or vibro-tactile feedback, has not been clearly explored. The purpose of this paper is to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Within the last decade, several groups have made impressive progress along both non-invasive and invasive routes. Gonzalez et al (2012) has shown that providing hand configuration via audio cues improves performance and reduces mental loading (González et al, 2010). Shehata et al (2018a) has shown that providing pattern recognition error improves the ability to learn internal models and results in an accompanying improvement in performance.…”
Section: Continuous Feedback For Real-time Controlmentioning
confidence: 99%
“…Within the last decade, several groups have made impressive progress along both non-invasive and invasive routes. Gonzalez et al (2012) has shown that providing hand configuration via audio cues improves performance and reduces mental loading (González et al, 2010). Shehata et al (2018a) has shown that providing pattern recognition error improves the ability to learn internal models and results in an accompanying improvement in performance.…”
Section: Continuous Feedback For Real-time Controlmentioning
confidence: 99%
“…If there are cerebellar differences in ASD, the integration and response to feedback may be challenged or require additional accommodation. Since auditory feedback has been utilized to aid in proprioceptive muscular control (Thaut et al, 1999a; González and Yu, 2009; González et al, 2010), rhythmic auditory stimuli may create a feed-forward interaction directly influencing motor output in a predictive way (Zatorre et al, 2007). This would provide the person with ASD an accommodation facilitating more efficient and fluid movement without over-reliance on proprioceptive feedback.…”
Section: Can Auditory Rhythm Enhance Motor Regulation In Asdmentioning
confidence: 99%
“…Neural interfaces for prosthetics are heavily researched. Electrode implants and reinnervation, [3][4][5][6] vibrotactile feedback, [7][8][9] and audio feedback 2,[10][11][12] have all been used in place of cutaneous and proprioceptive feedback in order to reduce the limitations of and reliance on visual feedback. Additionally, multimodal schemes demonstrate success with respect to ease of use, learnability, and performance 13 of both simple and complex motor tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the audio feedback architecture used in this study has proven to successfully aid users in discriminating between different types of objects, illustrating the adaptability and feasibility of the system. 2 Other investigations into audio feedback mechanisms indicate it is not only an effective agent for conveying force feedback to the user of a prosthetic hand, but also provides the user with an easily-learned and highly adaptive knowledge of the feedback, [10][11][12] augmenting task performance. 20 The current study shows that the feedback system is highly effective in assisting grasping tasks, provides users with more stable control, and supports previous research on the feedback method.…”
Section: Introductionmentioning
confidence: 99%